2011
DOI: 10.4049/jimmunol.1003389
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Ku70 Is a Novel Cytosolic DNA Sensor That Induces Type III Rather Than Type I IFN

Abstract: Cytosolic foreign DNA is detected by pattern recognition receptors and mainly induces Type-I IFN production. We found that transfection of different types of DNA into various untreated cells induces Type-III IFN (IFN-lambda1) rather than Type-I IFN, indicating the presence of uncharacterized DNA sensor(s). A pull-down assay using cytosolic proteins identified that Ku70 and Ku80 are the DNA binding proteins. The knockdown studies and the reporter assay revealed that Ku70 is a novel DNA sensor inducing the IFN-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(218 citation statements)
references
References 25 publications
8
204
0
1
Order By: Relevance
“…As a third example, DNA-dependent protein kinase, which is well established to play a central role in the nonhomologous end joining pathway of DNA repair (66), is also reported to interact with DNA in the cytoplasm and to be essential for the full induction of innate immune responses to DNA and DNA viruses in fibroblasts (61,67,68). Ferguson et al found that the DNA-dependent protein kinase subunit Ku70 is in a complex with STING in resting cells, but this interaction is abrogated following DNA stimulation (61).…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Other mentioning
confidence: 99%
“…As a third example, DNA-dependent protein kinase, which is well established to play a central role in the nonhomologous end joining pathway of DNA repair (66), is also reported to interact with DNA in the cytoplasm and to be essential for the full induction of innate immune responses to DNA and DNA viruses in fibroblasts (61,67,68). Ferguson et al found that the DNA-dependent protein kinase subunit Ku70 is in a complex with STING in resting cells, but this interaction is abrogated following DNA stimulation (61).…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Other mentioning
confidence: 99%
“…Reverse transcription was performed using SuperScript first strand synthesis system for RT-PCR (Invitrogen) as previously described (43). Real time quantitative PCR was performed as previously described (48). All probes were obtained from Applied Biosystems.…”
Section: Cd4mentioning
confidence: 99%
“…These results coupled with the structural observations open up the possibility that IFI16 participates in DNA repair. The recently reported participation of DNA-dependent protein kinase (DNA-PK) and Ku70, proteins primarily implicated in repair of damaged DNA, in the induction of IFN-1 production via the IRF1/IRF7 pathway upon transfection of DNA in HEK293 cells, fibroblasts, murine macrophages, and dendritic cells (DCs) (79,80) further suggests the need to investigate a role for the HIN proteins in DNA damage repair. It is tempting to speculate that the hydrogen bonds donated by lysines of the HIN domain to bases are part of a repair process initiated for fixing DNA damaged by ionization radiation.…”
Section: Unexplained Structural Insightsmentioning
confidence: 99%